Azide trapping of metallocarbenes: generation of reactive C-acylimines and domino trapping with nucleophiles - Bott, Tina; Atienza, Bren Jordan; West, F. G. (My University, 2014)
Azide-tethered diazocarbonyl compounds undergo copper-catalyzed conversion to transient C-acylimines. These reactive intermediates can be trapped with a variety of carbon nucleophiles, giving rise to complex 3-indolinone frameworks, including those with adjacent tetra-substituted carbon centers, in a single transformation.
Keywords: azide-tethered diazocarbonyl; C-acylimines; nitrogen heterocycles; tertiary amine; carbonyl ylides; Schmidt rearrangement; aziridination of electron-deficient alkenes; dinitrogen; betaine; nucleophile